John R. Taylor. Language in the Mind. Part II. / Kalba mąstyme. II dalis. Translated by Živilė Nemickienė - Nemickienė, Živilė (Respectus Philologicus, 2014)
Original article: John R. Taylor. Language in the mind
Keywords: none